2014
DOI: 10.1002/zaac.201400048
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the Chemistry of the Cyclopentadienyl Complex [Cp∧RuCl2]2 (“Cp‐roof” = η5‐1‐Methoxy‐2,4‐tert‐butyl‐3‐neopentylcyclopentadienyl)

Abstract: Abstract. The dimeric ruthenium complex [Cp ∧ RuCl 2 ] 2 is easily accessible in a one-pot reaction from RuCl 3 (solv) n and tert-butylacetylene. It features sterically very demanding "Cp-roof" ligands (Cp ∧ = η 5 -1-methoxy-2,4-tert-butyl-3-neopentylcyclopentadienyl), which impart a unique reactivity. Herein we describe the synthesis and the char-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 88 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…In contrast, that of 9a shows a highly distorted tetraazadiene moiety: N2–N3 bond is longer than the N1–N2 bond but shorter than the N3–N4 bond. The Ru–N bond (1.7459(19) Å) in 8a is clearly shorter than those in the tetraazadiene complexes and comparable to that (1.718(3) Å) of an analogous ruthenium imido complex [Cp^RuCl­(NAd)] . The coordination mode of the imido ligand in 8a (Ru–N–C angle 168.76(16) o ) is almost linear.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, that of 9a shows a highly distorted tetraazadiene moiety: N2–N3 bond is longer than the N1–N2 bond but shorter than the N3–N4 bond. The Ru–N bond (1.7459(19) Å) in 8a is clearly shorter than those in the tetraazadiene complexes and comparable to that (1.718(3) Å) of an analogous ruthenium imido complex [Cp^RuCl­(NAd)] . The coordination mode of the imido ligand in 8a (Ru–N–C angle 168.76(16) o ) is almost linear.…”
Section: Resultsmentioning
confidence: 82%
“…Furthermore, the addition of aryl azides to the solution provided ruthenium 1,4-diaryltetraazadiene complexes ( 7a – c ). Although several ruthenium complexes containing imido ligands have been reported, which are coordinated to one or two ruthenium centers, , only one cyclopentadienyl ruthenium imido complex, [Cp^RuCl­(NAd)] (Ad = adamantyl), has been reported by Severin and co-workers without reactivity investigation . This result inspired us that the use of bulky aryl azides would give the ruthenium imido complexes, which are less sterically congested than the corresponding ruthenium tetraazadiene complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic method was published by Severin et al and applied with minor modifications by reducing the temperature from 145 °C to 130 °C and increasing the reaction time to 7 minutes (original 3 min). The yields are in the same range as reported.…”
Section: Methodsmentioning
confidence: 99%
“…Severin et al reported that a mixed-ligand trichloridobridged diruthenium complex, [Cp*Ru(μ-Cl) 3 Ru(p-cymene)], is formed quantitatively upon mixing [Cp*RuCl] 4 and [(pcymene)RuCl 2 ] 2 . 33,34 On the basis of their observations, we succeeded in the exclusive preparation of a corresponding trihydrido-bridged diruthenium complex, [Cp ‡ Ru(μ-H) 3 Ru(pcymene)] (2a), using the 2-propanol/base method (Scheme 1a). 35 However, when [(C 6 H 6 )RuCl 2 ] 2 was employed, a mixture of mixed-ligand di-and triruthenium complexes, [Cp ‡ Ru(μ-H) 3 Ru(C 6 H 6 )] (2b) and [(Cp ‡ Ru) 2 {(C 6 H 6 )Ru}-(μ-H) 4 (μ 3 -H)] (3b), was obtained.…”
Section: ■ Introductionmentioning
confidence: 99%